Christian Culture and Society in Later Catholic England
1 online resource (730 pages)
Keywords: This book in memory of F. Donald Logan explores different aspects of Christian culture and society in England from the twelfth to the sixteenth century. Although this period has traditionally been interpreted in terms of decline and decay, this excessively gloomy picture has slowly given way over the last eighty years or so to a more positive view of Christian civilization during these centuries. The twenty-two studies brought together here seek to build on this ongoing reassessment of Later Catholic England, especially in those areas in which Professor Logan himself had done so much to deepen our understanding of Christian English society. Contributors are: Travis Baker, Caroline Barron, Nicholas Bennett, Barbara Bombi, Paul Brand, Janet Burton, James G. Clark, Karen Corsano, Virginia Davis, Charles Donahue Jr, Anne J. Duggan, Joan Greatrex, Diana Greenway, Michael Haren, R.H. Helmholz, Philippa Hoskin, Henry Ansgar Kelly, Frederik Pedersen, Seymour Phillips, Michael J.P. Robson, Jens Röhrkasten, Jane Sayers, R.N. Swanson, Daniel Williman, and Patrick Zutshi.